Factorial Study on the Evaluation of Formulation Variables on the Dissolution Rate of Etoricoxib Tablets - Chowdary, K.P.R.; Tarakaramarao, Ch. (Asian Journal of Chemistry, 2010)
The individual main and combined effects of commonly used binders, disintegrants and β- cyclodextrin on the dissolution rate of etoricoxib tablets were evaluated in a 23 factorial study. Etoricoxib tablets were formulated employing selected combinations of binder, disintegrant and β-cyclodextrin as per 23 factorial design and the tablets were evaluated for various physical properties, dissolution rate (k1) and dissolution efficiency (DE10). Dissolution parameters (K1 and DE10) were subjected to ANOVA of factorial design. The individual main effects of binder, disintegrant and β-cyclodextrin on the dissolution rate (K1) were significant (p < 0.05). Whereas all combined (or interaction) effects were not significant (p > 0.05). The individual main effects of binders and β-cyclodextrin on the dissolution efficiency (DE10) were significant (p < 0.05). The main effects of disintegrant and all combined effects on DE10 were not significant (p > 0.05). Tablets formulated employing poly(vinyl pyrrolidone) as binder and potato starch as disintegrant gave highest dissolution rate of etoricoxib, 95 % in 1 h.